Análises físico-químicas de pães isentos de glúten utilizando farinhas de arroz, sorgo e teff - Queiroz, Jociane Bruna (2022)
Adherence to a gluten-free diet, necessary in the case of celiac disease, is hampered by food monotony, among other factors. On the other hand, the ability to use rice flour, sorghum and teff in human food is great. In order to elaborate and characterize glutenfree breads for people with celiac disease, the objective of this work was to verify the physicochemical characteristics of gluten-free bread formulations made with rice, sorghum and teff flours. The parameters, pH, humidity, specific volume, color and texture profile were evaluated. The formulation containing rice flour was characterized as being light in color (close to white), high specific volume, less hardness and chewiness, greater elasticity, cohesiveness and resilience. The bread made with sorghum flour had a dark color, as well as the bread made with teff flour and with a mixture of the three flours. The formulation with teff flour had lower specific volume, moisture and pH and greater chewability. The flour mixture (optimized formulation) positively influenced the characteristic results of the breads, indicating that this mixture has the potential to be used in the development of gluten-free breads.